2000
DOI: 10.1128/iai.68.3.1312-1318.2000
|View full text |Cite
|
Sign up to set email alerts
|

The CD40/CD40 Ligand Interaction Is Required for Resistance to Toxoplasmic Encephalitis

Abstract: Since the CD40/CD40 ligand (CD40L) interaction is involved in the regulation of macrophage production of interleukin 12 (IL-12) and T-cell production of gamma interferon (IFN-␥), effector cell functions associated with resistance to Toxoplasma gondii, the role of CD40L in immunity to this parasite was assessed. Infection of C57BL/6 mice with T. gondii results in an upregulation of CD40 expression on accessory cell populations at local sites of infection as well as in lymphoid tissues. Splenocytes from C57BL/6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 46 publications
4
126
0
4
Order By: Relevance
“…For example CD40-CD40L signalling appears to be sufficient for in vitro and in vivo killing of T. gondii independently of IFN-g or reactive nitrogen species [47,48]. Importantly, CD40/ CD40L signalling is critical for protection against TE with CD40L À/À mice demonstrating increased parasite proliferation [49].…”
Section: (C-f) Magnification Of the Area Depicted By The Box In (A) mentioning
confidence: 99%
See 1 more Smart Citation
“…For example CD40-CD40L signalling appears to be sufficient for in vitro and in vivo killing of T. gondii independently of IFN-g or reactive nitrogen species [47,48]. Importantly, CD40/ CD40L signalling is critical for protection against TE with CD40L À/À mice demonstrating increased parasite proliferation [49].…”
Section: (C-f) Magnification Of the Area Depicted By The Box In (A) mentioning
confidence: 99%
“…For example CD40-CD40L signalling appears to be sufficient for in vitro and in vivo killing of T. gondii independently of IFN-g or reactive nitrogen species [47,48]. Importantly, CD40/ CD40L signalling is critical for protection against TE with CD40L À/À mice demonstrating increased parasite proliferation [49].In conclusion, during the course of our studies T1/ST2 was shown to be upregulated during T. gondii infection in the brain and demonstrated to have a protective role in resistant BALB/c mice as infected T1/ST2 À/À BALB/c mice showed increased susceptibility in comparison with infected WT mice. The increased susceptibility of T1/ST2 À/À mice was related to increased brain pathology that correlated with both increased parasite burden and greater cerebral expression of IFN-g, iNOS and TNF-a.…”
mentioning
confidence: 99%
“…The role of macrophages/microglia as effector cells against T. gondii, the fact that mice deficient in the CD40 -CD154 pathway are susceptible to cerebral toxoplasmosis despite unimpaired upregulation of IFN-γ together with the demonstration that CD40 induces autophagic killing of T. gondii independently of IFN-γ/NOS2 strongly suggest a paradigm where two arms of immunity: one dependent on IFN-γ/NOS2 and another dependent of CD40-induced autophagy are required to control T. gondii in the brain. This paradigm can explain why IFN-γ is insufficient for control of T. gondii in neural tissue (Yap et al 1998, Reichmann et al 2000.…”
Section: Potential Relevance Of Cd40-induced Autophagy In T Gondii Imentioning
confidence: 99%
“…However, studies in mouse models of T. gondii infection indicate that this pathway also activates mechanisms of host resistance that act independently of IFN-γ (Reichmann 2000). CD154 -/-mice develop toxoplasmic encephalitis despite upregulation of IFN-γ in the brain that is similar to that of infected wild-type mice (Reichmann et al 2000).…”
Section: Cd40 and The Immune Response Against T Gondiimentioning
confidence: 99%
See 1 more Smart Citation